Biosynthesis of a G-Quadruplex—forming sequence and its stabilization by ligands - Carvalho, Josué Leandro de Oliveira e (2015)
In addition to the Watson and Crick B-form duplex DNA, G-quadruplexes are four-stranded DNA structures formed in vivo by the self-assembly of guanine-rich sequences. These can be formed by one, two or four separate strands of DNA and present a diversity of topologies, defined by the strand orientation, loop size and sequence. G-quadruplexes can be found in telomeres, immunoglobulin switch regions and gene promoter regions. The biological relevant location on the genome makes these high-order structures an attractive target for drug design and the development of highly specific ligands that bind and stabilize G-quadruplex with therapeutic activity. Herein, the biosynthesis of a novel G-rich quadruplex-forming DNA sequence 58Sγ3 is described by plasmid amplification. The recovery and purification of 58Sγ3 oligonucleotide using size-exclusion chromatography is presented. The G-quadruplex formation is promoted and its topology is determined by circular dichroism. The stabilization of the G-quadruplex structure with quinoline and naphthalene-based derivatives is studied using melting analysis, G4-FID and PCR-stop assays. The results suggest that 58Sγ3 folds into a parallel-stranded G-quadruplex structure in 500 mM KCl buffer and that naphthalene-based ligands bind and stabilize the G-quadruplex structure. The ligands are also found to be quadruplex-specific over duplex DNA and inhibit Taq DNA polymerase. This work provides evidence for G-quadruplex formation within the immunoglobulin switch regions. Furthermore, it is suggested that the novel ligands here reported act as potent specific G-quadruplex binders and may also potentially be used to inhibit genes transcription in tumor cells.